The isolated and combined effects of selected physical activity and ibuprofen on delayed-onset muscle soreness - Rahnama, N.; Rahmani-Nia, F.; Ebrahim, K. (Journal of Sports Sciences, 2005)
Delayed-onset muscle soreness refers to the skeletal muscle pain that is experienced following eccentric exercise. The aim of the present study was to examine the physiological effects of physical activity with or without ibuprofen on delayed onset muscle soreness. Forty-four non-athletic male volunteers (age 24.3±2.4 years) were randomly assigned to one of four groups: physical activity (n=11), ibuprofen (n=11), physical activity and ibuprofen (combination, n=11), or control (n=11). The physical activity programme comprised 5min of walking and jogging, 10min of static stretching of the hands and shoulder girdle, and 5min of concentric movements with sub-maximal contractions. The total amount of ibuprofen consumed by a single individual was 2800mg; this was taken from 1h before the eccentric actions up to 48h after it. Delayed onset muscle soreness was induced by performing 70 eccentric contractions of the biceps muscle of the non-dominant side on a modified arm curl machine. Perceived muscle soreness, maximal eccentric contraction, creatine kinase enzyme activity and elbow range of motion were assessed 1h before and 1, 24 and 48h after the eccentric actions. The results indicated that, after the eccentric actions, soreness increased (P<0.001) across time in all groups, with the highest values being recorded at 24h. At 24 and 48h, greater soreness (P<0.001) was observed in the control group than in the physical activity and combination groups. After the eccentric actions, creatine kinase increased and was elevated (P<0.001) compared with baseline in all groups, with values returning to baseline in the physical activity and combination groups by 48h. However, creatine kinase in the control and ibuprofen groups was still significantly higher than at baseline after 48h. Creatine kinase was higher (P<0.001) in the control group than in physical activity and combination groups at 24 and 48h. There was also a reduction (P<0.001) in elbow range of motion across time. This reduction in elbow range of motion was greater (P<0.001) in the control and ibuprofen groups than in the physical activity and combination groups at 1, 24 and 48h. The reduction in maximum eccentric contraction was greater (P<0.001) in the control and ibuprofen groups than in the physical activity group at 24 and 48h and the combination group at 48h. In conclusion, the results add to our understanding of the effects of physical activity and the combination of physical activity and ibuprofen in reducing the severity of muscle soreness induced by eccentric exercise. Physical activity conducted before eccentric exercise alleviates muscle soreness. Our results indicate that physical activity with or without ibuprofen helps to prevent delayed-onset muscle soreness.